Business forecasting with forecastX - Wilson, J. Holton 1942-; Keating, Barry 1945- (McGraw-Hill/Irwin, 2009)
Presents a broad-based survey of business forecasting methods including subjective and objective approaches. This title includes Forecast X software updated for Excel 2007 and Vista.